2020
DOI: 10.1371/journal.pone.0238891
|View full text |Cite
|
Sign up to set email alerts
|

Extended spectrum beta lactamase producing bacteria among outpatients with ear infection at FelegeHiwot Referral Hospital, North West Ethiopia

Abstract: Background Antibiotic resistant bacteria particularly extended-spectrum beta lactamase (ESBL) producing are of major concern for management of outpatients. They can spread rapidly and are associated with poor patient outcome. However, there is scarcity of information on ear infection with ESBL producing bacteria in Ethiopia. Therefore, this study investigates the prevalence of ear infection with ESBL producing bacteria among outpatients attending Felegehiwot Referral Hospital, Northwest Ethiopia. Methods A hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This was consistent with the study conducted in Bahir Dar, where MDR prevalence was reported as 43%. 52 In this study, 50.9% and 38.2% of Gram-negative and Gram-positive isolates were MDR, respectively. Worldwide, there is an increasing population of MDR bacteria, which is becoming a serious concern for healthcare professionals and the population at large.…”
Section: Discussionmentioning
confidence: 53%
“…This was consistent with the study conducted in Bahir Dar, where MDR prevalence was reported as 43%. 52 In this study, 50.9% and 38.2% of Gram-negative and Gram-positive isolates were MDR, respectively. Worldwide, there is an increasing population of MDR bacteria, which is becoming a serious concern for healthcare professionals and the population at large.…”
Section: Discussionmentioning
confidence: 53%
“…Moderate to high resistance (50 to 75%) was observed against Ciprofloxacin, Ceftriaxone, Ceftazidime and Amoxicillin/Clavulanate and our results corroborate with others regarding gram-negative bacterial susceptibility. 17 , 18 , 20 , 23 Although Cefepime, the 4 th generation cephalosporin turned out to be good with 67 to 78% susceptibility but 3 rd generation cephalosporins like Ceftazidime and Ceftriaxone were found unsatisfactory. Likewise, Ciprofloxacin, a frequently used fluroquinolone was also found to be less efficacious with resistance ranging from 35 to 50% against both gram-positive and negative isolates, which coincides to some but contradicts others.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 7 Although P. aeruginosa has been reported to be the leading cause of CSOM followed by S. aureus by many investigators but variation in bacterial profile and frequency is well documented. 10 , 11 , 20 The conducive environment of middle ear cavity may favour the growth of P. aeruginosa but etiological agents of CSOM differs substantially with regards to time and place and also factors like variation in climate, socioeconomic status and patient’s self-hygiene play important role. 11 We observed polymicrobial infections in 7.3% cases, which is a very common occurrence in CSOM and many studies have reported mixed pathogens including bacteria and fungus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the tendency to use inanimate objects to remove Open access earwax can be attributed to the increased proportion of ESBL and MRSA, as these inanimate objects are often found in environments that may be contaminated with ESBL-producing bacteria and MRSA. 25 Almost all isolated bacteria (93%) were resistant to amoxicillin/clavulanic acid. Nearly three-quarters of Gramnegative bacteria were resistant to ceftazidime, and about half were resistant to trimethoprim-sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 99%